Conceptualizing Mano Dura in Latin America - Dammert-Guardia, L (Cambridge University Press, 2025)
Latin American governments are increasingly adopting mano dura initiatives to combat gangs, organized crime, and insecurity. While mano dura has been a concept of increasing empirical interest, there seems to be limited conceptual clarity about the wide spectrum of strategies developed to combat crime and associated fear. This article proposes a definition of mano dura that has three different dimensions, each of them containing specific elements. The form of mano dura depends on formal, informal, and rhetorical practices. Drawing on 46 scholarly works in the social sciences, we develop our definition anchored in the knowledge of Latin American policing strategies, contributions on responses to crime in the region, and the conceptual development literature. With the purpose of supplementing our effort to standardize the usage of the term with the need to retain a degree of conceptual differentiation, we also offer a stylized model to better classify policing strategies in Latin America. In our stylized model, the numerous ways policies and narratives as well as their implementation (or not) interact can be grouped into four broad categories: full mano dura, institutional mano dura, performative mano dura, and covert mano dura. © The Author(s), 2024. Published by Cambridge University Press on behalf of University of Miami.